A new species of Lucilia Robineau-Desvoidy (Diptera, Calliphoridae) from the Amazon region and its potential distribution areas - Whitworth, Terry L.; Amat, Eduardo (Zootaxa, 2023)
Lucilia amazonia, sp. nov. from the Amazon region of Colombia and Brazil is described based on morphology. This species appears to be limited to the Amazon region and is quite distinctive and unlike other Lucilia in the region. A key to the species is provided following the Lucilia key in Whitworth (2014). Based on the distribution observed, its likely distribution is predicted.